PENERAPAN PEMBELAJARAN KOOPERATIF TIPE STAD UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR SISWA PADA POKOK BAHASAN KELARUTAN DAN HASIL KALI KELARUTAN DI KELAS XI IPA 5 SMAN 9 PEKANBARU - Indri Meidina; Asmadi M.Noer; Betty Holiwarni (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
Abstract: This is a classroom action research. This research is an attempt to improve student learning activities in chemistry on class XI IPA 5 of SMAN 9 Pekanbaru by applying cooperative model of Student Teams Achievement Division (STAD). Improved student learning activity is the activity of asking questions, submit answers or opinions, working on exersices and group discussion, quiz too. There were 36 students of XI IPA 5 SMAN 9 Pekanbaru involved in research that did in four cycles of learning. Each cycle consisted of one meetings through four stages of implementation: planning, action, observation, and reflection. Data collection techniques using observation and test. The result of action showed that activity percentage of students increased and reached the success indicator. Activity of student percentage in first cycle 55,20% with criteria enough, second cycle 62,15% with criteria good, three cycle 66,14% with criteria good and fourth cycle 73,43% with criteria good. The percentage of learning outcomes also increased and reached the success indicator. The average percentage in 1st, 2nd, 3rd, and 4th followed by 79,79&, 84,03%, 82,83%, and 99,03%. Based on the result obtained, it can be concluded that application cooperative model of STAD can to increase the activity and student learning outcomes.Keyword : Cooperative Model of STAD, Student Activities, Learning Outcomes Student